High Inflammatory Burden: A Potential Cause of Myocardial Injury in Critically Ill Patients With COVID-19 - Song, Yanjun; Gao, Peng; Ran, Tian; Qian, Hao; Guo, Fan; Chang, Long; Wu, Wei; Zhang, Shuyang (Frontiers in Cardiovascular Medicine, 2020)
Background Myocardial injury (MI) was a severe complication of novel coronavirus disease (COVID-19) and inflammation was suggested as a potential cause for MI. However, the correlation of MI with inflammation in COVID-19 patients is not revealed so far. Method This retrospective single-center cohort study enrolled 64 critically ill patients with COVID-19. Patients were categorized into two groups by the presence of MI on admission. Demographic data, clinical characteristics, laboratory tests, treatments and outcomes were analyzed in this study. Result Of these patients, the mean age was 64.8±12.2 years old, and 34 (53.1%) were diagnosed with MI. Compared with non-MI patients, MI patients were older (67.8±10.3 vs 61.3±13.3 years; P=0.033), combined with more cardiovascular (CV) risk factors like smoking ( 16 [47.06%] vs 7 [23.33%]; P=0.048) and more likely to develop CV comorbidities (13 [38.2%] vs 2 [6.7%]; P=0.003). Scores of APACHE II (median [interquartile range (IQR)]19.0 [13.25-25.0] vs 13.0 [9.25-18.75]; P=0.005) and SOFA systems (7.0 [5.0-10.0] vs 4.5 [3.0-6.0]; P<0.001) were significantly higher in MI-group. Besides, patients with MI had higher mortality than those without MI (29 [85.29%] vs 18 [60.00%]; P =0.022). Cox regression suggested that MI was an independent risk factor for high mortality during the time from admission to death (hazard ratio, 2.18 [95% confidence interval (CI), 1.17-4.04]; P=0.014). Plasma levels of high-sensitivity C-reactive protein (hs-CRP), interleukin (IL)-1β, IL-2R, IL-6, IL-8, IL-10 and tumor necrosis factor-α (TNF-α) exceeded the normal limitation, and levels of hs-CRP, IL-2R, IL-6, IL-8 and TNF-α were statistically higher in MI-group than non-MI patients. Logistic regression showed that plasma levels of hs-CRP (odds ratio (OR) 1.01, [95% CI, 1.00-1.02]; P=0.010), IL-6 (OR 1.02, [95% CI, 1.00-1.04]; P=0.028) and TNF-α (OR 1.1, [95% CI, 1.00-1.21]; P=0.048) were positively correlated with the incidence of MI. Conclusion MI is a common complication served as an independent risk factor for high mortality rate among in-ICU patients with COVID-19. High inflammatory burden may play an important role in the occurrence of MI.